BdCV1-Encoded P3 Silencing Suppressor Identification and Its Roles in Botryosphaeria dothidea, Causing Pear Ring Rot Disease - Shanshan Li; Haodong Zhu; Ying He; Ni Hong; Guoping Wang; Liping Wang (Cells, 2023)
Pear ring rot disease is an important branch disease, caused by Botryosphaeria dothidea. With the discovery of fungal viruses, the use of their attenuated properties for biological control provides a new strategy for the biological control of fungal disease. RNA silencing is a major antiviral defense mechanism in plants, insects, and fungi. Viruses encode and utilize RNA silencing suppressors to suppress host defenses. Previous studies revealed that Botryosphaeria dothidea chrysovirus 1 (BdCV1) exhibited weak pathogenicity and could activate host gene silencing by infecting B. dothidea. The aim of our study was to investigate whether BdCV1 can encode a silencing suppressor and what effect it has on the host. In this study, the capability of silencing inhibitory activity of four BdCV1-encoded proteins was analyzed, and the P3 protein was identified as a BdCV1 RNA silencing suppressor in the exotic host Nicotiana benthamiana line 16c. In addition, we demonstrated that P3 could inhibit local silencing, block systemic RNA silencing, and induce the necrosis reaction of tobacco leaves. Furthermore, overexpression of P3 could slow down the growth rate and reduce the pathogenicity of B. dothidea, and to some extent affect the expression level of RNA silencing components and virus-derived siRNAs (vsiRNAs). Combined with transcriptomic analysis, P3 had an effect on the gene expression and biological process of B. dothidea. The obtained results provide new theoretical information for further study of interaction between BdCV1 P3 as a potential silencing suppressor and B. dothidea.